Health Assessment of BUMN Banks in Indonesia Using RGEC (Risk Profile, Good Corporate Governance, Earnings, And Capital) Period 2014-2024 - Dewi, Iriana Kusuma (Asian Journal of Management Analytics, 2025)
This study evaluates the financial health of five Indonesian state-owned banks—Mandiri, BRI, BNI, BTN, and BSI—implementing the RGEC model (Risk Profile, Good Corporate Governance, Earnings, and Capital) during 2020–2024. A descriptive quantitative approach was used with data from published financial reports. Findings show that all banks maintained a healthy status. NPL ratios were below 5%, and LDR values ranged from 85%–100%, indicating sound risk and liquidity management. GCG ratings were consistently at PK-2, reflecting good governance. Profitability was generally strong, with ROA, ROE, and NIM meeting ideal standards, though BTN showed less efficiency (high BOPO). All banks had CAR values well above regulatory minimums, signaling strong capital positions.